Primary disability due to neoplasms in Ukraine: structure, trends, influencing factors - A.V. Ipatov; I.Y. Khaniukova; О.М. Moroz; N.A. Sanina (Medičnì Perspektivi)
A full study was conducted using the statistical method of research in order to analyze the status and structure of primary disability of the adult population of the regions of Ukraine due to tumors in the period ща 2010–2019 and identify the causes that affect the indicators of primary disability and regional characteristics. We have performed the analysis of expanded statistical information regarding disability in Ukraine with the help of the "Report on the causes of disability, indications for medical, professional and social rehabilitation" (form № 14, approved by order of the Ministry of Health of Ukraine in coordination with State Statistics Committee of Ukraine dated 10.07.2007 № 378) within 24 regions of Ukraine and Kyiv over the last ten years. In addition, the correlation analysis was performed using Microsoft Excel© to find the connection between primary disability due to neoplasms and a number of medical and social factors using Pearson-Brave correlation coefficient (r). Over the last ten years, the rates of primary disability due to neoplasms and malignant tumors of both adults and able-bodied population have been increasing steadily. They have always been among the top three causes of disability in Ukraine. However, cardiovascular diseases occupied the first place over the last 27 years. In 2019, tumors took the first place. Fluctuations in primary disability due to neoplasms are connected with a number of medical and non-medical causes. The main ones are morbidity, prevalence of neoplasms, number of beds in cancer dispensaries and availability of specialized oncology medical expert commissions in the region, changes in legislation regarding criteria for assessing disability groups. In the structure of primary disability due to neoplasms people of working age (40-60 years) dominate, their number varies by year, but the tendency to predominance persists Among the disability groups a severe second disability group dominates, which indicates a late diagnosis due to untimely treatment of these people and the predominance of the so-called "neglected" forms of the disease. This trend takes place during the observation period of all ten years.  The highest rates of primary disability due to neoplasms are also stable throughout the ten-year observation period and are observed in the regions that are considered the most affected by Chornobyl disaster: Kyiv region, Kyiv, Zhytomyr, Chernihiv, Volyn, Rivne. However, the increase in this indicator in Poltava region over the last three years is not entirely motivated. The obtained results will be the basis for the development of national and regional measures for the rehabilitation of people with disabilities caused by tumors and contribute to public funds saving due to their targeted distribution in regions and keeping labor resources.